Rolling Audit: Patient’s Satistfaction for Services Provided in ENT Ward - Neupane, Yogesh; Guragain, RPS; Khallilullah, S; Prakash, S (Nepalese Journal of ENT Head and Neck Surgery, 2013)
Nepalese Journal of ENT Head and Neck Surgery, Vol. 3 Issue 1 (Jan-June 2012) Page 17-20 DOI: http://dx.doi.org/10.3126/njenthns.v3i1.8184